Perceived ease of use dan perceived usefulness dalam loyalitas pelanggan: Efek mediasi customer satisfaction pada mahasiswa pengguna aplikasi Gojek di Yogyakarta - Makbul, Reza Sofian; Lukitaningsih, Ambar; Ningrum , Nonik Kusuma (Nur Science Institute, 2025)
Application-based online transportation services, such as Gojek, have become an important part of Indonesian people's lives, especially among students, due to their ease in meeting daily mobility needs. However, in the 2020–2023 period, there was a significant decline in the use of Gojek, with on-demand business segment transactions decreasing by 8.47% to reach IDR 40.38 trillion. This study aims to analyze the effect of perceived ease of use and perceived usefulness on customer loyalty, with customer satisfaction as a mediating variable, in the context of students in Yogyakarta. The analysis method used path analysis with 120 respondents. The results showed that perceived ease of use did not significantly affect customer loyalty, while perceived usefulness had a positive and significant effect. In addition, customer satisfaction was a significant mediating variable in the relationship. These findings provide insight for online transportation service companies in designing more effective business strategies to increase customer loyalty, increase user satisfaction, and face fierce competition in the ever-growing online transportation industry.